2008
DOI: 10.1007/s00264-008-0562-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of tibial rotation in fixed and mobile bearing total knee arthroplasty using computer navigation

Abstract: Tibial rotation is an important aspect of knee function and can be altered after total knee arthroplasty (TKA). These alterations include decreased internal rotation with knee flexion as compared to the normal state and paradoxical external rotation with flexion. Mobile bearing total knee prostheses may allow greater unconstrained tibial rotation. I compared tibial rotation after fixed bearing or mobile bearing total knee arthroplasty in 82 patients who underwent TKA with the tibia cut first technique to ascer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 26 publications
(32 reference statements)
2
13
0
Order By: Relevance
“…These results are similar to those reported in fluoroscopic studies in which a single leg lunge activity is performed. [6][7][8]12 The more demanding STS activity analyzed in this report seems to result in similar findings to an asymmetrically performed lunge maneuver.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…These results are similar to those reported in fluoroscopic studies in which a single leg lunge activity is performed. [6][7][8]12 The more demanding STS activity analyzed in this report seems to result in similar findings to an asymmetrically performed lunge maneuver.…”
Section: Discussionsupporting
confidence: 71%
“…10,11 Several studies have shown that the normal screw-home mechanism, external rotation of the tibia with knee extension, is altered after TKA. [6][7][8]12 However, these studies have been criticized as they do not apply to normal daily activity. For example, the movement reported was for non-weight-bearing activity or during a courtesy lunge type of maneuver.…”
Section: Introductionmentioning
confidence: 99%
“…Computer assisted orthopaedic surgery (CAOS) was first introduced in 1999 by Krackow et al Its objective is to improve the accuracy of implant positioning and extremity alignment [11][12][13]. CAOS for total knee arthroplasty (TKA) is gaining popularity among orthopaedic surgeons.…”
Section: Introductionmentioning
confidence: 99%
“…A few kinematic studies have been undertaken to investigate the kinematics of osteoarthritic knee preoperatively [2,3,11,15,20], but we are unaware of any kinematic studies that addressed the relationship between the kinematic variables of knees before and after TKA. Initially, navigation systems were used to improve implant alignment during TKA [10,13,14], but more recently a number of kinematic studies have used navigation systems to investigate passive knee kinematics in patients with osteoarthritis during TKA [3,5,11,20,21]. However, it still remains unclear how the preoperative knee kinematics affect the knee kinematics after TKA.…”
Section: Introductionmentioning
confidence: 99%